Sustainability Analysis of Tuna (Thunnus sp.) Fishery in Sendang Biru, Malang Regency - Febdya Nur Wahyu Nandita; Budi Setiawan; Fitria Dina Riana (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
Tuna capture fisheries have a very important value and meaning for the socio-economic life of coastal communities, either directly or indirectly. On the other hand, the catch of tuna has decreased from an ecological aspect based on the exploited status, production, and the value of CpUE (Cath per Unit Effort), the length of the fish caught, and the amount. The research objective was to analyze the sustainability status of tuna fisheries from 3 dimensions. This study was a survey of 76 respondents in the Sendang Biru Malang districts. The method used the Multi-Dimensional Scaling (MDS) analysis using the software Rapfish (Rapid Appraisal for Fisheries). The results showed that the sustainability status to be seen from 3 dimensions, ecology, economic, and social, which showed that the level of sustainability of tuna fishery from the economic and social dimensions was enough sustainable. For the ecological dimensions, it shows less sustainability. In general, the level of sustainability of tuna fishery in the Sendang Biru is enough sustainable. There need activities related to environmental conservation to increase ecological sustainability. In addition, it is necessary to hold counseling and training on aquatic ecosystems so that they are utilized in the short term and in the long term.